Rumah joglo sebagai identitas visual arsitektur tradisional - syifa, bilqis syifaur (Maliki Interdisciplinary Journal, 2024)
Joglo houses, as one of Indonesia's traditional architectural cultural heritages, have an important role in representing the visual identity of Javanese society. With its distinctive structure and inherent symbolic values, the Joglo House is a manifestation of rich local aesthetics and philosophy. This research aims to explore the main design elements of the Joglo House, such as the curved joglo roof, upright main columns, and ornaments that decorate the structural parts. The analysis was carried out using a descriptive approach and literature study to understand how these elements function to reflect the social and cultural characteristics of Javanese society. The research results show that the Joglo House not only functions as a place to live but also as a symbol of community identity and strength. The use of local materials and traditional construction techniques strengthens the connection between the architecture and the surrounding environment. Therefore, Rumah Joglo becomes more than just a physical building; it is a visual representation of the values, history and culture passed down from generation to generation. It is hoped that this research can increase appreciation of the diversity of traditional architecture and encourage efforts to preserve and rejuvenate Joglo houses in the modern era.